Analysis of the Implementation of the Al-Qur'an Memorization Policy at the Muhammadiyah Elementary Madrasah (MIM) Sumampir, Rembang, Purbalingga - Miftahul Jannah; Sabarudin (al-Afkar, Journal For Islamic Studies, 2026)
This research is based on the awareness of the importance of education during childhood because education during that period will determine the success of education in the future. Madrasah Ibtidaiyah Muhammadiyah (MIM) Sumampir, Rembang, Purbalingga is one of the elementary educational institutions that has innovated in the curriculum by incorporating the Al-Qur'an memorization program into their educational curriculum. The success of MIM Sumampir in implementing this program is interesting to be studied further. This study aims to analyze the implementation of the Al-Qur'an memorization policy at MIM Sumampir, Rembang, Purbalingga. The data analysis technique used in this study is the Miles and Huberman analysis model, including data condensation, data display, and conclusion drawing/verification. Many previous studies have discussed the implementation of the tahfiz program in formal educational institutions. The novelty in this study lies in the research subjects due to differences in time and place and in the theory used for the analysis tool. The results of the study indicate that the implementation of the tahfiz policy as a flagship program at MIM Sumampir has been running well when viewed using Edwards III's theory of the variables influencing the policy implementation process. The results indicate that MIM Sumampir has succeeded in directing each variable towards quality improvement, although several aspects still need to be evaluated.